A full-scale experimental study on single dwelling burning behavior of informal settlement. (March 2021) - Wang, Yu; Beshir, Mohamed; Cicione, Antonio; Hadden, Rory; Krajcovic, Michal; Rush, David
Abstract: Approximately one billion people globally live in informal settlements with a large potential fire risk, where a single dwelling fire may result in a very large urban conflagration leaving hundreds, if not thousands, of people homeless. What is not well understood, however, is how fires in informal settlement dwellings develop and spread, and what influence the dwelling boundary has on these two areas. In this work, four different real-scale compartments were constructed and ignited under a large fire calorimeter hood. The cases include a typical thin metal-walled dwelling (baseline), a no leakage dwelling, a dwelling lined with cardboard and a dwelling with highly insulated walls. The fuel locations, fuel loads of 25 kg/m 2, ignition method and ambient conditions were kept identical in four experiments. Important parameters of compartment fire development, such as heat release rate, gas temperatures, fuel mass loss rate, wall and ceiling temperature were recorded. To investigate the fire spread mechanism between dwellings, the incident radiation heat flux around the dwellings and projection flame length were measured as well. It was found that the boundary conditions in informal settlement significantly affect the fire dynamics and fire spread of informal settlement, and that current analytical/empirical equations are not capturing accurately experimental observations. Highlights: Full-scale experiments indicate the fire development and spread in the informal settlement. Compartment boundary conditions significantly differ the flashover occurrence. Informal settlement dwellings have higher peak HRR and but lower temperature. The collapses of the wall or roof should not be neglected. Current analytical equations are not capturing informal settlement burning behavior.